2006
DOI: 10.1021/jp056700d
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization of cis,cis-1,4-Diphenyl-1,3-butadiene in the Solid State:  The Bicycle-Pedal Mechanism

Abstract: The cis-trans photoisomerization of crystalline or powdered cis,cis-1,4-diphenyl-1,3-butadiene (cc-DPB) was studied at room temperature. The progress of the reaction was monitored by fluorescence spectroscopy, powder X-ray diffraction, 1H NMR and HPLC. High conversions (up to 90%) to the trans,trans isomer were observed in a crystal to crystal reaction. Formation of the cis,trans isomer, the sole product obtained in solution and in very viscous glassy media at 77 K is entirely suppressed in the solid state. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 31 publications
5
42
0
Order By: Relevance
“…Figure 4 shows spectra typical of the trans conformer. A photoisomerization process is observed for the DPB molecules in DCA similar to that observed for DPB crystals by Saltiel et al, [21] even though we found that its evolution is much slower than that observed for the DPB molecules cast from solution (see the Supporting Information). Moreover, while in DPB films a decrease of the overall PL intensity is detected after photoisomerization, in DCA ICs the emission intensity is stable after prolonged lightexposure times.…”
Section: Dca Host-guest Thin Filmssupporting
confidence: 88%
See 1 more Smart Citation
“…Figure 4 shows spectra typical of the trans conformer. A photoisomerization process is observed for the DPB molecules in DCA similar to that observed for DPB crystals by Saltiel et al, [21] even though we found that its evolution is much slower than that observed for the DPB molecules cast from solution (see the Supporting Information). Moreover, while in DPB films a decrease of the overall PL intensity is detected after photoisomerization, in DCA ICs the emission intensity is stable after prolonged lightexposure times.…”
Section: Dca Host-guest Thin Filmssupporting
confidence: 88%
“…The different absorption and PL properties of DPB s-trans and s-cis conformers have been used to study their equilibrium in solution [20] and photoisomerization processes in the solid state. [21] According to the preparation conditions of DPB and DPB-DCA, PL spectra of different mixtures of the two conformers are obtained (see the Supporting Information). Figure 4 shows spectra typical of the trans conformer.…”
Section: Dca Host-guest Thin Filmsmentioning
confidence: 99%
“…[1] This appealing switching phenomenon can be associated with a reversible modification of the geometrical structure, redox potential, dielectric constant, magnetic susceptibility and refractive index. [2] Photoinduced processes can involve interesting phenomena such as redox reaction, [3] electronhole pair generation, [4] spin crossover, [5] coordination change, [6] photocyclisation, [2] photoisomerisation, [7] tautomerisation [8] and bond cleavage. [8] Solid-state photochromism, which is rarely encountered, enables prospective potential applications in information storage, [9,10] molecular machines, [11] optical switches, displays, sensors [12] and in nonlinear optics.…”
Section: Introductionmentioning
confidence: 99%
“…[42] N-Salicylidene aniline derivatives are not the only possible candidates for light-induced information storage applications. Many others photochromic molecules have been described by using a large range of chemical reaction such as redox reactions, [43] electron-hole pair generation, [44] spin crossover, [45] coordination change, [46] photocyclization, [43] photoisomerization, [47] bond cleavage [48] and so on. Nevertheless, solid-state photochromism appears to be rare and only a few systems fulfill criteria for data storage applications.…”
Section: Introductionmentioning
confidence: 99%